A novel maltooligosaccharide-forming α-amylase from Bacillus cereus and its application in the preparation of maltopentaose product. (May 2023) - Pan, Shiyou; Wang, Guiping; Sun, Chang; Du, Liqin; Qi, Xianghui; Wei, Yutuo
Abstract: Maltooligosaccharides (MOS) have become a prominent market in the pharma and food industries due to their excellent bio-preservative and prebiotic properties. However, producing specific maltooligosaccharides like maltopentaose (G5) is relatively tedious and expensive. Here, a novel maltooligosaccharide-forming α-amylase from Bacillus cereus (BcMFAse) was characterized and exhibited a specific activity of 1965.0 ± 9.7 U/mg. The BcMFAse principally produced G5 by hydrolyzing soluble starch, with a maximum G5 yield of 215.8 ± 5.9 g/kg starch, accounting for 63.8 % of the saccharide mixture. The enzymatic hydrolysate was purified by AB-8 macroporous resin column chromatography. Briefly, 1.0 mL adsorbate containing 486.6 g/L total saccharides with deionized water elution at a flow rate of 0.7 mL/min and column temperature of 55 °C. Afterward, G5 was enriched up to 95.4 % purity, and 72.2 % was recovered in solution. The proposed process was simulated by SuperPro Designer software, and the remarkable economic results included a payback period of 0.08 years and an internal rate of return of 294.6 %. This study represented that BcMFAse could be a promising candidate for applications in the food and pharma fields. It first provided a high-efficiency process for producing > 90 % pure G5, which was economically attractive on an industrial scale. Graphical Abstract: ga1 Highlights: A novel maltooligosaccharide-forming α-amylase (BcMFAse) was firstly reported. BcMFAse had 1965 U/mg of amylase activity and 63.8 % of maltopentaose specificity. A high-efficiency process for producing pure maltopentaose was developed. 95.4 % of maltopentaose purity was achieved by AB-8 macroporous resin purification. Techno-economic analysis of high-purity maltopentaose production was conducted.